Gravity derived crustal thickness model of Botswana: Its implication for the Mw 6.5 April 3, 2017, Botswana earthquake - Chisenga, Chikondi; Van der Meijde, Mark; Yan, Jianguo; Fadel, Islam; Atekwana, Estella A.; Steffen, Rebekka; Ramotoroko, Calistus (Tectonophysics, 2020)
Botswana experienced a Mw 6.5 earthquake on 3rd April 2017, the second largest earthquake event in Botswana's recorded history. This earthquake occurred within the Limpopo-Shashe Belt, ~350 km southeast of the seismically active Okavango Rift Zone. The region has no historical record of large magnitude earthquakes or active faults. The occurrence of this earthquake was unexpected and underscores our limited understanding of the crustal configuration of Botswana and highlight that neotectonic activity is not only confined to the Okavango Rift Zone. To address this knowledge gap, we applied a regularized inversion algorithm to the Bouguer gravity data to construct a high-resolution crustal thickness map of Botswana. The produced crustal thickness map shows a thinner crust (35–40 km) underlying the Okavango Rift Zone and sedimentary basins, whereas thicker crust (41–46 km) underlies the cratonic regions and orogenic belts. Our results also show localized zone of relatively thinner crust (~40 km), one of which is located along the edge of the Kaapvaal Craton within the MW 6.5 Botswana earthquake region. Based on our result, we propose a mechanism of the Botswana Earthquake that integrates crustal thickness information with elevated heat flow as the result of the thermal fluid from East African Rift System, and extensional forces predicted by the local stress regime. The epicentral region is therefore suggested to be a possible area of tectonic reactivation, which is caused by multiple factors that could lead to future intraplate earthquakes in this region. •First nationwide gravity derived crustal thickness model for Botswana.•The Congo Craton boundary in northwestern Botswana is presented for the first time from gravity data.•A proposed causative mechanism for the April 3, 2017 6.5 Mw Botswana earthquake.